(untitled) (American & British Studies Annual, 2022)
E. L. Doctorow became world-famous primarily for his novel Ragtime (1975), which references a distinct style of playing the piano that had a profound impact on the development of jazz. Music also plays a principal role in a number of the author’s other works. This paper explores the role of music in one of his later novels, City of God (2000), with a focus on selected scenes in which music is represented. From the viewpoint of different modes of music in literature, namely the thematization of music, the sound layer and the musicalization of fiction, this contribution examines the emotions elicited in the protagonists in the scenes in question, as well as the atmosphere that the music creates or accentuates. It also takes into account which musical instruments are employed, including the symbolic meaning that one of them, the violin, carries. Furthermore, an investigation is presented as to what extent musical elements from other novels by E. L. Doctorow can be found, and in which respects this novel is unique. In City of God, the lyrics of jazz tunes emerge throughout the novel, thus the importance of this motif is discussed in detail along with the attention devoted to other major manifestations of music in this literary work.